Associations Between Consumption of Different Vegetable Types and Depressive Symptoms in Japanese Workers: A Cross-Sectional Study - Gong Q; Momma H; Cui Y; Huang C; Niu K; Nagatomi R (Dove Medical Press, 2022)
Qiang Gong,1 Haruki Momma,1 Yufei Cui,1,2 Cong Huang,3 Kaijun Niu,4 Ryoichi Nagatomi1,5 1Department of Medicine and Science in Sports and Exercise, Tohoku University Graduate School of Medicine, Sendai, Japan; 2Institute of Exercise Epidemiology and Department of Physical Education, Huaiyin Institute of Technology, Huaian, People's Republic of China; 3Department of Physical Education, Zhejiang University, Hangzhou, People's Republic of China; 4Department of Epidemiology, School of Public Health, Tianjin Medical University, Tianjin, People's Republic of China; 5Division of Biomedical Engineering for Health & Welfare, Tohoku University Graduate School of Biomedical Engineering, Sendai, JapanCorrespondence: Ryoichi Nagatomi, Division of Biomedical Engineering for Health & Welfare, Tohoku University Graduate School of Biomedical Engineering, 2-1 Seiryo-machi, Aoba-ku, Sendai, 980-8575, Japan, Tel/Fax + 81-22-717-8586, Email nagatomi@med.tohoku.ac.jpPurpose: Vegetable intake is an important part of our everyday diet and is associated with many positive health outcomes. Although previous studies have investigated the association between vegetable consumption and depressive symptoms among various populations, no study has examined this association in the adult working population. The present study investigated whether the frequency of consumption of a specific type of vegetable is associated with the prevalence of depressive symptoms in Japanese adult workers.Participants and Methods: The final participants consisted of 1724 Japanese adults, and a cross-sectional study was conducted to analyze the results. The frequency of vegetable consumption and depressive symptoms was evaluated using a brief-type self-administered diet history questionnaire and the Zung Self-Rating Depression Scale (SDS), respectively. The association between the variables was examined using Poisson regression analysis. Age-stratified analysis was performed, and SDS cut-off values of 45 and 50 were used to perform a sensitivity analysis.Results: After adjustment for covariates, including age, body mass index, sociodemographic and lifestyle-related variables, health condition, C-reactive protein, and other dietary variables, an inverse association was found between tomato product consumption and the prevalence of depressive symptoms among men (P for trend < 0.01); however, no significant association was found for other vegetable types. For women, there was no association between the frequency of consumption of any of the vegetable types and the prevalence of depressive symptoms. The results were confirmed by the age-stratified analysis for both genders.Conclusion: Consumption of tomato products may help alleviate depressive symptoms, regardless of differences in dietary culture among men.Keywords: vegetables, depression, Japan, adults, workers, tomato products